The use of Trojan-horse drug delivery system in managing periodontitis - Zoltán Géczi; Ivett Róth; Zsófia Kőhidai; László Kőhidai; Khaled Mukaddam; Péter Hermann; Dániel Végh; Tivadar Zelles (Elsevier, 2023)
ABSTRACT: The aim of this review is to evaluate the possibility of delivering a silver-acid complex via a Trojan-horse mechanism for managing periodontits. We theroised that the complex could be an effective treatment option for bacterial inflammatory processes in the oral cavity. Searches were conducted using MEDLINE, Embase, Web of Science Core Collection, and Google Scholar search engines. We also reviewed several reference lists of the included studies or relevant reviews identified by the search. By using Medical Subject Headings (MeSH) terminology, a comprehensive search was performed for the following keywords: silver, folic acid, periodontitis, macrophages, Trojan-horse mechanism, toxicity, and targeting. Using the keywords mentioned earlier, we selected 110 articles and after appropriate elimination the review was written based on 37 papers. Accordingly the we noted that silver isons were an effective approach to kill oral pathogens. Secondly the Trojan-horse mechanism. could be used by macrophages (as the Trojan horse) to deliver silver ions in large quantities to the inflammatory focus to kill the periodontopathogens. The Trojan-horse mechanism has never been described in the field of dentistry before. The proposed novel approach using the principle of Trojan Horse delivery of drugs/chemicals could be used to manage oral inflammatory conditions. This method can be used to supplement regular treatments.